The Performance of the Proposed Topologies Under Uniform and Non-Uniform Traffic Conditions: Importance of Traffic Matrix in Designing Regular Virtual Topologies (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This paper studies the deployment of such architecturesas regular virtual topologies in arbitrary physical networks. The inputs to thevirtual topology design problem are the physical topology, the traffic matrixand the regular topology. This gives insight into the relative importance ofthe physical topology and traffic matrix when designing a regular virtualtopology for optical packet switching. Regardless of the approach adopted, theproblem is intractable, and hence, heuristics must be used to find (near)optimal solutions expeditiously. An important conclusion of this paper is thatthe traffic matrix plays a less significant role than is conventionallyassumed, and only a marginal penalty is incurred by disregarding it in severalof the traffic cases considered. In fact, it was found that it is possible todesign the regular virtual topology without using the traffic matrix, and yet,the solution is close to optimal for a range of traffic scenarios andrelatively immune to traffic condition.